The Economics of Female Piety in Early Sufism - Arin Salamah-Qudsi (Religions, 2021)
This paper examines the economics of female piety between the third/ninth and sixth/twelfth centuries. It traces Sufi approaches to poverty and working for a living (kasb) as well as kasb’s intersection with marriage and women. Rereading Sufi and non-Sufi biographies and historiographies reveals that there were wealthy women who initiated marriage with renowned Sufis to gain spiritual blessings, and others who financially supported their husbands. While the piety of male Sufis was usually asserted through material poverty, the piety of female mystics was asserted through wealth and almsgiving. This paper examines this piety through different female kinships—whether mothers, wives or sisters. Similar to the spousal support of wives for their husbands, sisters very often acted as an impressive backup system for their Sufi brothers. Mothers, however, effected a great socio-religious impact through the cherished principles of a mother’s right to control her son and a son’s duty to venerate his mother. This devotion was often constraining financially and Sufis needed to pay attention to the financial implications while still pursuing progress on the Sufi path.